Genetic analysis of p60v-src domains involved in the induction of different cell transformation parameters. - Jove, R (1986)
The expression of p60v-src in chicken cells infected with Rous sarcoma virus causes stimulation of cell proliferation, morphological alteration, and anchorage independence. PA101 and PA104 are temperature-sensitive variants encoding mutant p60v-src proteins that are partially defective in the induction of these transformation parameters. To define the structural basis for the transformation defectiveness of the p60v-src mutants, the v-src genes of PA101 and PA104 were molecularly cloned and analyzed. Amino- and carboxy-terminal coding regions of the cloned mutant genes were exchanged with the corresponding regions of cloned wild-type v-src and chicken c-src genes, reconstructed into viral DNA, and expressed in infected cells maintained at various temperatures. This analysis revealed that lesions within the tyrosine kinase domains of the two mutant proteins confer temperature sensitivity on all three transformation functions of p60v-src. An amino-terminal region of the PA101 mutant protein, which coincides with the proposed modulatory domain and appears to interact with the kinase domain, affects morphological alteration in a temperature-independent manner. Our results suggest that the function of the kinase domain is essential to all three parameters examined, whereas the amino-terminal domain is important in determining cell morphology.